2020
DOI: 10.1122/1.5132395
|View full text |Cite
|
Sign up to set email alerts
|

The role of friction in the yielding of adhesive non-Brownian suspensions

Abstract: Yielding behavior is well known in attractive colloidal suspensions. Adhesive non-Brownian suspensions, in which the interparticle bonds are due to finite-size contacts, also show yielding behavior. We use a combination of steady-state, oscillatory and shear-reversal rheology to probe the physical origins of yielding in the latter class of materials, and find that yielding is not simply a matter of breaking adhesive bonds, but involves unjamming from a shear-jammed state in which the micro-structure has adapte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 46 publications
4
49
0
Order By: Relevance
“…Our findings therefore encourage future simulation studies to include realistic constraints and relationships between sliding and rolling friction coefficients and adhesive forces. Moreover, we present a route where the variations of the contact properties are reversible and externally controlled during shear and do not require a modification of the composition of the materials, i.e., via the addition of surfactants 45 , 55 and small molecules (e.g., urea) 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings therefore encourage future simulation studies to include realistic constraints and relationships between sliding and rolling friction coefficients and adhesive forces. Moreover, we present a route where the variations of the contact properties are reversible and externally controlled during shear and do not require a modification of the composition of the materials, i.e., via the addition of surfactants 45 , 55 and small molecules (e.g., urea) 27 .…”
Section: Discussionmentioning
confidence: 99%
“…1), as observed. Importantly, adhesive constraints that limit inter-particle rolling can also lower φ J (Guy et al 2018;Richards et al 2020). These are broken above a critical torque, M a , set by the attractive force between particles and a surface length scale that pins the contact (Heim et al 1999).…”
Section: Constraint Rheology Of Suspensionsmentioning
confidence: 99%
“…If both constraints operate, jamming occurs at a lower concentration, 'adhesive loose packing', φ J (a = 1, f = 1) = φ alp < φ acp . This critical volume fraction, which is possibly related to rigidity percolation (Richards et al 2020), is not yet precisely known; one simulation returns φ alp ≈ 0.14 (Liu et al 2017). The various jamming points are summarised in Table 1. In any actual suspension, 0 ≤ f(σ/σ * ), a(σ/σ * ) ≤ 1, and φ J (σ ) depends on the degree to which frictional/adhesive contacts are formed/broken by the applied stress.…”
Section: Constraint Rheology Of Suspensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that shear-thinning observed in concentrated NBSs was due either to the presence of adhesion forces between particles [70] or to the decrease in the interparticle friction coefficient when the shear stress increases [15,17] or both [71]. These two effects lead to variations in viscosity with shear stress that have very different patterns.…”
Section: Influence Of Surface Functionalization On the Rheological Properties Of Nbss Of µPs Mp1 Mp3 And Mp5mentioning
confidence: 99%